Morphological Study of Affixation in Sasak Selaparang Dialect - Wahyu Kamil Syarifaturrahman; Zainuddin Abdussamad; Lela Rahmawati (LPPM Universitas Bumigora Mataram, 2022)
Language has many important roles in our life especially for communication. We can imagine how our life will be without language. Every nation has its own language such as Indonesia with its own language and spoken by their native speaker for example Japanese spoken by Japanese society, Balinese by Balinese society and Sasak by Sasak society in Lombok West of Nusa Tenggara. Although Indonesia consist of thousand tribes and many different local languages, Indonesia has Indonesia language as its national language and spoken by all Indonesians. Actually this study gives some descriptions about affixation in Sasak especially in selaparang dialect which has a specific purpose to find out the form of affixation in Sasak in selaparang dialect. Furthermore, the method that is used in this study is descriptive qualitative method by giving arguments about the aspect of affixation in Sasak. Finally, the result of this study is found 18 (eighteen) affixes in Selaparang dialect which is divided into 4 (four) kinds of affixation namely 7 (seven) prefixes (be-, peN-, per-,pe-, nge-, te-,and me-); 2 (two) infixes (-em-, and –eg-); 1 (one) suffix (-an/ -ang); 8 (eight) simulfixes (be-an/-ang, peN- an/-ang, per- an/-ang,pe- an/-ang, nge- an/-ang, te- an/-ang, ke- an/-ang, and me- an/-ang).